Efficient synthesis of potent anti-tubercular drug candidate BM212 - More, N. A.; Patil, M. D.; Garud, D. R.; Gajbhiye, J. M. (Rasayan Journal of Chemistry, 2016)
A novel five step total synthesis route for an anti-tubercular drug BM212 starting from 4-chlorophenacyl bromide was developed with 48% overall yield. The synthesis is amiable for the synthesis of biologically active derivatives of BM 212.

Convenient synthesis of the enantiomerically pure (S)-2,4-dihydroxybutyl-4-hydroxybenzoate using hydrolytic kinetic resolution - More, N. A.; Jadhao, N. L.; Garud, D. R.; Gajbhiye, J. M. (Synthetic Communications, 2018)
(S)-2,4-Dihydroxybutyl-4-hydroxybenzoate was prepared in an extremely simple and practical way with high enantiomeric excess (99% ee) using Jacobsen’s Hydrolytic Kinetic Resolution technique as a key step and source of chirality.